ESTRATÉGIAS DE COPING ENTRE JOVENS ATLETAS: UMA REVISÃO DE ESCOPO - Sandro Torales Schulz (2023)
Introduction: Young athletes often face different types of pressures related to competitions, professional, personal, or family relationships. Managing these psychological threats is essential to ensure satisfactory sports outcomes. Thus, understanding how athletes cope with psychosocial challenges can lead to increased sports productivity, improved focus and concentration, as well as more assertive decision-making. Objective: This study aimed to identify and map coping strategies used by young athletes in the scientific literature and their possible relationships with athletes' age, gender, sport discipline, and competitive level. Methods: This is a scoping review that adopted the theoretical framework proposed by the Joanna Briggs Institute (JBI) and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review (PRISMA-ScR) guidelines. The Population-Concept-Context strategy was used to formulate the research question. The search was conducted in databases such as PUBMED, WEB OF SCIENCE, MEDLINE, LILACS, SCIELO, PsycINFO, Scopus, and SPORTDiscus, using terms like "youth athletes" OR "young athletes," "coping" OR "athletic coping" OR "coping strategies" OR "coping skills," and "Sports" OR "Athletics" OR "Athletic" OR "Youth Sports" NOT "Injuries," along with their respective equivalents in Portuguese and Spanish. The search was conducted independently by two researchers. Results: A total of 4,038 articles were retrieved from the database search, and 28 publications were analyzed after applying exclusion criteria. Out of the 28 articles, 22 (78.6%) studies used quantitative analyses, and 6 (21.4%) used qualitative analyses. The review revealed that young athletes generally employ emotion-focused coping strategies more frequently, while slightly older athletes tend to focus their efforts on cognitive strategies to change the stressful event (i.e., problem-focused coping). Boys tend to use more problem-focused coping strategies, while girls use more emotion- focused coping strategies and seek social support. Regarding the type of sport, athletes in individual sports tend to use coping strategies focused on emotion, such as seeking social support, in addition to strategies related to concentration. On the other hand, athletes in team sports more frequently employ problem-focused coping strategies related to improved sports performance. Athletes at higher competitive levels tend to apply problem-focused coping strategies more frequently, including emotional control, quick recovery from errors or failures, high performance in the face of challenges, mental planning and preparation, focus, confidence, and performance motivation. Conclusion: Coping strategies adopted by young athletes seem to differ based on gender, age, sport, and competitive level. There is a need for future longitudinal studies to analyze how young athletes generally deal with stress in the sports and competitive environment, as coping strategies change throughout life, necessitating constant updates.